Mechanical and Civil engineering graduates domain Knowledge and Life Skills for Employability - Patil, Rupesh J.; Charak, Kuldip S. (International Journal of Psychosocial Rehabilitation, 2020)
Employability of Engineering Graduates has become a biggest concern for the Institutions, Industries and related government agencies. Year by year, the Intake reduction of engineering institutesis becoming the problem of concern for the faculty’s career as well.This research paper is the portion of the research work in understanding and analyzing the employable parameters of engineering graduates from Maharashtra (India).The research work is based on the feedback of Alumnus of these colleges. Thestatistical analysis of employability parametershelps in arriving the solution.